Molecular identification of Leptospira spp. in urine samples from female water buffaloes. Preliminary results - Rosaura Pérez-Gil; Héctor Nava-Trujillo (Revista Científica)
Animal leptospirosis is a zoonotic disease that affects multiple domestic and wild species. It causes generalized vasculitis, which in pregnant females results in placentitis and triggers abortion. Furthermore, it causes hemoglobinuria, icterus (jaundice), and congestion in different mucosa. The objective of this study was to establish whether the occurrence of hemoglobinuria and changes in the pigmentation of the vaginal mucosa was associated with the presence of Leptospira spp. DNA in the urine. Therefore, 38 urine samples from lactating female buffaloes showing hemoglobinuria, alterations in the pigmentation of the vaginal mucosa, history of abortion, and low-weight calves were evaluated. Additionally, hematocrit was determined by blood centrifugation in a capillary tube, and the presence of hemoparasites was determined by staining of blood smears. The DNA of Leptospira spp. was detected by PCR using two pairs of primers for the markers G1-G2, derived from a sequence from the genomic library of L. interrogans serovar icterohaemorragiae, strain RGA, which was described by Gravekamp et al. (1993). Additionally, Internal 1 and Internal 2 were derived from the sequence of the gene encoding the LipL32 protein and specific to identify pathogenic leptospira, described by Haake et al. (2000). Data analysis was performed with R (Fisher’s exact test). The hematocrit mean was 21%, and all females were negative for hemoparasites (Anaplasma mar ginale, Babesia spp., and Trypanosoma spp.). The percentage of Leptospira spp. DNA-positive samples with at least one of the markers used was 63%. The marker G1-G2 detected more positive samples in comparison with the marker Internal 1-Internal 2 (60.5% vs 7.9%,  p<0.0001 respectively). A significant association was observed between the mucosa’s appearance and the presence of Leptospira spp. DNA in urine when the G1-G2 was used (p <0.0001). In the case of females with icteric vaginal mucosa, the percentage of positive samples (85%, 17/20, p = 0.001227) was higher than that in buffaloes with normal mucosa (26.66%, 4/15). In addition, in females with icteric vaginal mucosa, the odds of a positive sample for Leptospira spp. DNA (using the G1-G2 marker) were 14 (95% CI: 2.3427-119.1974) times more than in females with normal vaginal mucosa. There was no significant difference in the percentage of positive samples between buffaloes grouped as icteric mucosa, and congestive mucosa (p= 0.4529), nor between the females grouped as congestive and normal mucosa (p= 0.2451). When the Internal 1-2 marker was used, there was no association between the appearance of the mucosa and the percentage of buffaloes with Leptospira spp. DNA in the urine (p= 0.1714). The presence of hemoglobinuria was not associated with Lep tospira spp. DNA in the urine, regardless of the marker used for its detection (p>0.05). In conclusion, the data from this study indicates that the G1-G2 marker was more efficient in determining the presence of Leptospira spp. DNA in urine, and using this marker, the icteric vaginal mucosa is associated with Lep tospira spp. DNA in urine, thus suggesting that this clinical sign should be considered suggestive of the disease.